2020
DOI: 10.3389/fpsyg.2020.608426
|View full text |Cite
|
Sign up to set email alerts
|

Less Is More—Cyclists-Triathlete’s 30 min Cycling Time-Trial Performance Is Impaired With Multiple Feedback Compared to a Single Feedback

Abstract: Purpose: The purpose of this article was to (i) compare different modes of feedback (multiple vs. single) on 30 min cycling time-trial performance in non-cyclist’s and cyclists-triathletes, and (ii) investigate cyclists-triathlete’s information acquisition.Methods: 20 participants (10 non-cyclists, 10 cyclists-triathletes) performed two 30 min self-paced cycling time-trials (TT, ∼5–7 days apart) with either a single feedback (elapsed time) or multiple feedback (power output, elapsed distance, elapsed time, cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In this study, the participants perceived both muscle activation and relaxation in the agonist–antagonist muscles as a single beep or an overlap of different beeps. It has been reported that the simultaneous multiple information of biomechanical output decreases pedaling endurance performance due to information overload (Bayne et al, 2020 ). Auditory feedback from two muscles could result in multiple information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the participants perceived both muscle activation and relaxation in the agonist–antagonist muscles as a single beep or an overlap of different beeps. It has been reported that the simultaneous multiple information of biomechanical output decreases pedaling endurance performance due to information overload (Bayne et al, 2020 ). Auditory feedback from two muscles could result in multiple information.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the simultaneous multiple information of biomechanical output decreases pedaling endurance performance due to information overload (Bayne et al, 2020). Auditory feedback from two muscles could result in multiple information.…”
Section: Improving Emg-bf To Reduce Muscle Co-contractionmentioning
confidence: 99%
“…In this study, participants identified both the activation and relaxation of agonist-antagonist muscles either as a single beep or a combination of different beeps. Previous research indicates that the simultaneous processing of multiple pieces of biomechanical output information can decrease pedaling endurance performance due to information overload [29]. The auditory feedback from two muscles could indeed lead to the presentation of multiple pieces of information.…”
Section: Future Issues For Auditory Emg-bf To Improve Muscle Co-contr...mentioning
confidence: 99%